2001
DOI: 10.1074/jbc.m007495200
|View full text |Cite
|
Sign up to set email alerts
|

Human Factor H-related Protein 5 (FHR-5)

Abstract: A novel human plasma protein has been identified as a universal component of complement deposits, when complement is detected immunohistochemically in vivo. The protein is homologous to complement factor H and related proteins and has been designated factor H-related protein 5 (FHR-5). FHR-5 was identified by a monoclonal antibody raised using pathologic human glomerular preparations as the immunogen. FHR-5 was purified by affinity chromatography from complementlysed erythrocytes, and the peptide sequence was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…4). By comparison to the areas mapped in human factor H that confer binding activity for C3b, FHR-5 has two potential binding sites for C3b (8,10), and therefore, it is not surprising that human FHR-5 has the ability to bind C3b (26). The same basic SCR structure and capacity to bind C3b is true for rat FHR, as we have shown here.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…4). By comparison to the areas mapped in human factor H that confer binding activity for C3b, FHR-5 has two potential binding sites for C3b (8,10), and therefore, it is not surprising that human FHR-5 has the ability to bind C3b (26). The same basic SCR structure and capacity to bind C3b is true for rat FHR, as we have shown here.…”
Section: Discussionsupporting
confidence: 57%
“…This was possible because the K2.254 monoclonal antibody raised against diseased glomeruli reacted with FHR-5 and was used to isolate FHR-5 for peptide determination, knowledge of which was then used in a cloning strategy. In these studies, it was shown that FHR-5 mRNA could be produced by the liver and that FHR-5 protein could deposit on guinea pig erythrocytes during complement activation by whole serum (26). In follow-up studies on FHR-5, it was clear that FHR-5 was a prominent component of glomerular immune deposits, being present in 100% of cases of membranous nephropathy, IgA nephropathy, and lupus nephritis (27).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations